Desarrollo del pensamiento geométrico de niños de básica primaria a través de actividades lúdico-recreativas en el marco de un curso de extensión - Monsalve Rojas, César Augusto (Universidad Antonio Nariño, 2021)
The purpose of the research was to design and implement playful-recreational strategies to strengthen the development of geometric thinking in children in basic primary education. 13 students from different colleges and degrees participated, with ages between 7 and 11 years who were in an extension course of the Bachelor of Mathematics at the Antonio Nariño University. The methodology implemented was based on action research, which involved field work characterized by the observation, participation and reflection of the teacher for three months.